Energy storage systems for refrigerated warehouses. (December 2017) - Li, Xueqiang; Campana, Pietro Elia; Li, Hailong; Yan, Jinyue; Zhu, Kai
Abstract: To reduce the peak load, dynamic electricity price schemes have been widely used. Refrigerated warehouses consume a large amount of energy, most of which happens during the daytime due to the higher ambient temperature. This work evaluated the potential benefits of integrating energy storage in the refrigerated warehouses. Two types of energy storage systems have been considered, including a cold energy storage system and an electrical energy storage system. A dynamic model has been developed in TRNSYS to study the performance of those two energy storage systems and assess the benefits. Results show that using the cold energy storage to shift power consumption from daytime to nighttime can increase the energy efficiency of the refrigeration system. However, as the electrical energy storage system can shift more power consumption, it can achieve a large cost saving. Compared to the reference system without energy storage, the introductions of a cold energy storage system and an electrical energy storage system can reduce the operational cost by 10 and 53.7% respectively.